Assessment of Knowledge, Practices, and Challenges of Pharmaceuticals Inventory Control Among Pharmacy Professionals Working in Selected Public Health Facilities of West Arsi Zone, Oromia, Ethiopia. (January 2022) - Jobira, Tadesse; Abuye, Habtamu; Jemal, Awol; Gudeta, Tadesse
Background: Good pharmaceutical inventory control enables health facilities (HFs) to provide complete health care by ensuring the availability of safe, effective, and affordable pharmaceuticals and related supplies of the required quality, inadequate quantity, at the required place and at all times. It boosts patients' trust in the HFs and motivates working staff. However, it needs well-trained and skilled professionals. The aim of the current study was, therefore, assessing knowledge, practice, and challenges of pharmacy professionals conducting inventory control in selected public health facilities of West Arsi Zone, Oromia regional state for the year 2016 to 2018. Method: A mixed-methods study design was used to assess pharmacy professionals' knowledge, skills, and challenges in applying inventory management methods. A semi-structured questionnaire was implemented for quantitative, whereas an open-ended question was employed for key informants (KIs) to explore qualitative data. Result: Ninety percent of pharmacy professionals knew about VEN analysis concepts and 70% about ABC analysis. However, none of them had a concept of FSN and XYZ analysis. Among the respondents who knew the concept, 75% had gained knowledge through formal training and 10% of them learned from on-job training. When they asked about the methods of inventory control, 60% responded as they did not hear about it. Of those who said "Yes" on being asked to mention at least 1 method of it, 80% could not able to correctly mention the methods used in inventory control. However, 44%, 62.5%, and 75% of respondents had practiced ABC, VED, and ABC-VED matrix analysis respectively. The challenges that prevented these professionals from practicing pharmaceutical inventory control in their HFs were grouped into price-related, training-related, human resource-related, and managerial-related factors. Conclusion: Inventory control is the heart of the pharmaceutical supply system. Without its healthy action, HFs' goal attainment will not be viable. Problems of sick pharmaceutical inventory control are directly related to a lack of knowledge and appreciation of it by the concerned bodies. The current finding revealed almost all pharmacy professionals included in the study had little knowledge about how to manage their inventories. Managers' unwillingness to cooperate and facilitate necessary resources prevented the professionals from doing inventory control.